Attenuation of cGVHD by C5a/C5aR blockade is associated with increased frequency of Treg - Yulian Wang (Nature Portfolio, 2017)
Abstract C5aR signaling plays an important role in the regulation of T cell activation and alloimmune responses in chronic graft-versus-host disease (cGVHD). However, direct evidence of this modulation and the efficacy of C5aR blockade in the treatment of cGVHD have not been demonstrated. We observed higher expression of C5aR on both monocytes and T cells of patients with cGVHD compared with healthy controls and non-GVHD patients after allogeneic hematopoietic stem cell transplantation. Our data also demonstrated a significant negative correlation between C5aR expression and regulatory T cells (Treg) frequency in cGVHD patients, indicating a potential role of C5aR in the generation and regulation of Treg. In addition, an in vitro experiment revealed C5aR deficiency promoted the development of Treg whereas C5a activation abolished the differentiation of Treg. Importantly, we found C5aR blockade by PMX53 attenuated the pathology of cGVHD and improved the survival of cGVHD mice. PMX53 had a direct regulatory effect on Treg commitment and increased TGF-β1 expression. Thus, C5aR signaling may induce and intensify cGVHD by down-regulating Treg induction. The modulation of C5aR activation by PMX53 may provide a potential therapy for cGVHD.